COX-2 is required to mediate crosstalk of ROS-dependent activation of MAPK/NF-κB signaling with pro-inflammatory response and defense-related NO enhancement during challenge of macrophage-like cell line with Giardia duodenalis. - Yudan Zhao; Yongwu Yang; Min Liu; Xuening Qin; Xiran Yu; Huimin Zhao; Xiaoyun Li; Wei Li (Public Library of Science (PLoS), 2022)
Giardia duodenalis, the causative agent of giardiasis, is among the most important causes of waterborne diarrheal diseases around the world. Giardia infection may persist over extended periods with intestinal inflammation, although minimal. Cyclooxygenase (COX)-2 is well known as an important inducer of inflammatory response, while the role it played in noninvasive Giardia infection remains elusive. Here we investigated the regulatory function of COX-2 in Giardia-induced pro-inflammatory response and defense-related nitric oxide (NO) generation in macrophage-like cell line, and identified the potential regulators. We initially found that Giardia challenge induced up-regulation of IL-1β, IL-6, TNF-α, prostaglandin (PG) E2, and COX-2 in macrophages, and pretreatment of the cells with COX-2 inhibitor NS398 reduced expressions of those pro-inflammatory factors. It was also observed that COX-2 inhibition could attenuate the up-regulated NO release and inducible NO synthase (iNOS) expression induced by Giardia. We further confirmed that Giardia-induced COX-2 up-regulation was mediated by the phosphorylation of p38 and ERK1/2 MAPKs and NF-κB. In addition, inhibition of reactive oxygen species (ROS) by NAC was shown to repress Giardia-induced activation of MAPK/NF-κB signaling, up-regulation of COX-2 and iNOS, increased levels of PGE2 and NO release, and up-expressions of IL-1β, IL-6, and TNF-α. Collectively, in this study, we revealed a critical role of COX-2 in modulating pro-inflammatory response and defense-related NO production in Giardia-macrophage interactions, and this process was evident to be controlled by ROS-dependent activation of MAPK/NF-κB signaling. The results can deepen our knowledge of anti-Giardia inflammatory response and host defense mechanisms.